UTILIZATION OF WEBSITE AND GOOGLE FORM AS ONLINE ADMINISTRATIVE SERVICES AT THE FACULTY OF ENGINEERING, MUHAMMADIYAH UNIVERSITY OF WEST SUMATRA - Hariyadi, Mezia Kemala Sari, Dwi Pratiwi Wulandari, Edi Haskar , Kevry Ramdany, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since the Covid-19 pandemic period has had an impact on the implementation of learning and services for the world of education starting from the Elementary level to Higher Education, this has resulted in educators not being able to carry out face-to-face meetings in class and education personnel unable to do the maximum service to students/teachers/lecturers in schools or campus. So that one of the most appropriate steps is to establish that the learning process is carried out remotely and administrative services are online. This study took the subject of the Academic Community at the Faculty of Engineering, Muhammadiyah University of West Sumatra which is a descriptive study with a census sampling technique carried out from January 2021- June 2021. Online administrative services carried out at the Faculty of Engineering, Muhammadiyah University of West Sumatra are very effective and can prevent crowds during the Covid-19 Pandemic, from the results of research on online administrative services, 98.125% responded agreeing/benefiting from the online service and only 1.875% of respondents objected to online administrative services